Uphill ski skating technique modification during competition - Toftegaard, Ø.; Reid, R.; Gilgien, M.; Jacobsen, V.; Smith, G. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: In cross-country ski-skating, two skating techniques (V1 and V2) are used on moderate uphill terrain. V1 skating is typically used for steeper climbing while V2 is a higher speed technique for flat and rolling terrain. In recent years, there has been some emphasis on using V2 technique on steeper uphills. Comparisons have been made of V1 and V2 under controlled laboratory conditions with rollerskiing on a treadmill (Kvamme et al., 2005, Smith et al. 2009) but on-snow comparisons of the techniques during racing have not been made. This paper is a case study of two elite skiers during a World Cup race. Kinematic comparisons of their use of V1 and V2 skating techniques were made at a site during the race where it was expected that skiers would be transitioning from V2 to V1 technique.